Caracterização dos acidentes envolvendo motocicletas atendidas pelo samu, em Sobral-CE, de 2006 a 2012. - Vasconcelos, Ana Karina Barbosa (2013)
In the last decade there has been a significant increase in the purchase of vehicles, especially motorcycles, which in Ceará was 255.44%, concomitantly, there was an increase in the number of traffic accidents, about 320%. In the city of Sobral also there was a disorderly growth of both the number of motorcycles and in the number of accidents. The work aimed to characterize the temporal distribution of accidents involving motorcyclists in the city of Sobral, in the period 2006-2012, after the implementation of the SAMU and specific objectives: Addressing the epidemiologic characteristics of victims of motorcycle accidents, attended by SAMU sobral in the period 2006-2012, to describe the dynamics / kinetics involving trauma patients seen by SAMU and used motorcycles for transportation; Identify and describe the data pre-hospital mortality in Sobral. Study of quantitative and documentary approach, exploratory and descriptive, occurred in the city of Sobral, with 6483 occurrences with motorcycles attended by SAMU, in the period from 2006 to 2012, whose data were collected by searching the leaves of occurrence of the SAMU. The analysis was performed using SPSS, respecting the ethical principles of Resolution 196/96. Results: were 6483 accidents involving motorcycles in the years 2006 to 2012, the city of Sobral. 5,729 (78.5%) were aged 16-59 years, 4,644 (71.63%) were male, 1,381 (21.30%) occurred in the city center, 36 (0.55%) were women pregnant; 6,001 (92.56%) were rescued to the Hospital Santa Casa de Misericordia de Sobral; 4,951 (76.36%) wore helmets at the time of the accident and the state of drunkenness increased 3.33 times, going from 133 in 2006 to 443 in 2012. The causes of motorcycle accidents were: 2,808 (43.31%) falls motorcycle, 1,158 (17.73%) with car and bike collisions 1,064 (16.41%) with bike bike collisions. Collisions with bike bike maintained a stable pattern, with a decrease of 25.75% in 2012, consistent with the gradual replacement bike motorcycle. In relation to victims, the driver was the one that stood out, about 77%, with the appearance of the pedestrian with 7.63% and 7.48% with the cyclist. Of which 5,153 (79.48%) were rescued by the Basic Support Unit, 1,208 (18.63%) by Advanced Support Unit and 121 (1.86%) by Motolância. Among those who died, 170 were attended by SAMU, during the period 2006-2012. Were 90% of deaths occurred in men, among the main reasons of the deaths had the bike down (141 to 53.52%), 100 (58.82%) of the deaths occurred on site, with 141 (83%) were to the conductors. It is necessary to invest in the road network, adopt and maintain horizontal and vertical signage appropriate quantitative professional supervision commensurate with the size of the current fleet to the flow characteristics of vehicles, ensuring the effectiveness of traffic laws. It is also imperative society participation, especially for schools, churches, and especially the families who must take a starring role in the education process for